The Effect of Applying the Discovery Learning Model on Science-Fuelled Learning on Learning Outcomes of Grade III Students of SDN 1 Ploso - Kartika, Rizki Setya; Sukamti; Untari, Esti (Journal of Education for Sustainability and Diversity, 2023)
This research was conducted to determine whether or not the implementation of the Discovery Learning model influenced the learning outcomes of the cognitive aspects of class III students at SDN 1 Ploso, Pacitan District. A quantitative approach using the experimental method is used in this study. The population and sample in this study were 42 students, where class IIIA was the control class, and IIIB was the experimental class. Tests and documentation are data collection techniques in this study. Instrument testing techniques include validity test, reliability test, level of difficulty, and differential power. Prerequisite test t-tests and hypothetical tests are the data analysis techniques used. Prerequisite test through normality test, linearity test, and homogeneity test. To find out whether there is a difference in the pretest-posttest average scores of the two classes, a t-test is carried out. The hypothesis test is in the form of a simple linear regression test where the result is a significance value of 0.000 <0.05, so it can be concluded that the application of the Discovery Learning model affects the learning outcomes of the cognitive aspects of class III students at SDN 1 Ploso.